Peran Pendampingan Dalam Akselerasi Transformasi Digital UMKM di Desa Sumogawe - Dea Aulia Rahmi; Sri Mulyani Oktaviana Alifah; Qonita Sanal Barqiy Anafa Albab; Panca Reza Fauzi; Maulana Wahid Apriansah; Ahmad Zubaeri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2025)
The MIT 20 Posko 47 UIN Walisongo Community Service Program (KKN) aims to support the acceleration of digital transformation of MSMEs in Sumogawe Village, known as “Kampung Susu” (Milk Village) with great creative economic potential. Through a qualitative case study approach, this research analyzes the role of students as facilitators, educators, and motivators in assisting MSME actors. Data collection methods included in-depth interviews, participatory observation, and documentation studies, with data analysis following the Miles and Huberman model. The results showed that student assistance successfully increased the digital visibility of MSMEs through the implementation of Google My Business (GMB) and QRIS, strengthened business branding with Metromedia Technologies (MMT), and improved the digital literacy of business actors. Support from village officials and the enthusiasm of MSMEs were key contributing factors, although challenges such as time constraints, disparities in digital literacy, and uneven internet infrastructure still hindered the optimization of the program. This program contributed significantly to improving the competitiveness of MSMEs in the creative economy era and supported the achievement of sustainable development goals (SDGs).